Abraham's Family: a network of meaning in Judaism, Christianity, and Islam - Bormann, Lukas (Wissenschaftliche Untersuchungen zum Neuen Testament, 2018)
Cover -- Titel -- Preface -- Table of Contents -- Introduction -- PART I: ABRAHAM'S FAMILY IN THE OLD TESTAMENT -- Konrad Schmid (University of Zurich): Remembering and Reconstructing Abraham. Abraham's Family and the Literary History of the Pentateuch -- Antti Laato (Åbo Akademi University): The Abraham Story in Genesis and the Reigns of David and Solomon -- Magnar Kartveit (VID Specialized University, Stavanger): Abraham and Joseph in Samaritan Tradition -- Lotta Valve (Åbo Akademi University): The "Wooing of Rebekah" and the Methodological Rift between Tradition History and Reception History -- PART II: ABRAHAM'S FAMILY IN ANCIENT JEWISH LITERATURE -- Jacques T. A. G.M. van Ruiten (University of Groningen): Abraham's Family in the Book of Jubilees -- Aliyah El Mansy (University of Marburg): "He is perfect, he is a true man!" (Jub. 27:17). Constructions of Masculinities in Abraham's Family -- Jesper Høgenhaven (University of Copenhagen): Abraham and his Family in Qumran Biblical Exegesis -- Michael Becker (1958-2018) (University of Munich): Abraham and the Sacrifice of Isaac in Early Jewish and Christian Exegesis. Conceptual Patterns in Development -- Christian Noack (Schulzentrum Marienhöhe, Darmstadt): Abraham's Family in Philo -- PART III: ABRAHAM'S FAMILY IN THE NEW TESTAMENT -- Lukas Bormann (University of Marburg): Abraham as "Forefather" and his Family in Paul -- Angela Standhartinger (University of Marburg): Member of Abraham's Family? Hagar's Gender, Status, Ethnos, and Religion in Early Jewish and Christian Texts -- Christfried Böttrich (University of Greifswald): Abraham and his Children in Luke-Acts -- Guido Baltes (University of Marburg): The Prodigal Son and his Angry Brother. Jacob and Esau in a Parable of Jesus? -- J. Cornelis de Vos (University of Münster): Abraham's Family in the Epistle to the Hebrews